Marketing Communication Strategy of CV 06 Production in Increasing the Number of Events: A SWOT Analysis Approach - Tri Wahyu Ningsih; Yulia Pebrianti; Tsurayya Syarif Zain (Takaza Innovatix Labs Ltd., 2024)
CV 06 Production is an event organizer company operating since 2006, managing various events for both private and public sectors. With the growing demand for professional event services and increasing market competition, the company must develop a well-directed marketing communications strategy. The purpose of this study is to analyze the company's strengths, weaknesses, opportunities, and threats (SWOT), and to formulate appropriate marketing communication strategies to increase the number of events managed. This study employs a descriptive qualitative method, with data collected through observations, interviews, documentation, and questionnaires distributed to 20 clients. Data analysis is conducted using the IFAS, EFAS, SWOT, and Grand Strategy matrices. The IFAS matrix resulted in a score of +0.375, indicating stronger internal strengths. Meanwhile, the EFAS score of +1.15 shows that external opportunities outweigh threats. These results position the company in Quadrant I of the SWOT matrix, supporting the implementation of a growth-oriented strategy. Recommended strategies include optimizing digital media usage, developing an official website, enhancing internal coordination, and diversifying promotional channels. These approaches are expected to expand the company's market reach and sustainably increase its event portfolio.